AVALIAÇÃO DE PROPRIEDADES FÍSICAS E MECÂNICAS DE ARGAMASSAS DE GESSO RECICLADO PROVENIENTE DA APLICAÇÃO DE REVESTIMENTO INTERNO DE EDIFICAÇÃO - Alencar, Artur S.; Nunes, David B. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The plaster was incorporated as an internal building, because it is a cheap material and easy to handle, with a large generation of waste, causing environmental problems. Although there is a growing interest in the use of this residue as an inner seal coating, there is a certain lack of knowledge about its production technology as well as its behavior. This work analyzes physical and mechanical properties of natural gypsum mortar, used as reference, with those of recycled gypsum with impurities and with mortar of another gypsum without impurities, verifying compliance with current standards through laboratory tests. The results presented granulometry among the similar samples, not occurring great variation as a function of the calcination temperature. The consistency of the mortar despite the water / gypsum ratio is different, the recycled gypsum has demonstrated fluidity adequate to the handling according to the norm. The time of picking of the recycled gypsum presented time of beginning and end of handle near the one of the commercial gypsum. The recycled gypsum still presented inferior results regarding the mechanical resistance in relation to the gypsum commercialized, with the gypsum without impurities reaching an average closer to the reference.